Lower urinary tract symptoms and incident functional limitations among older community‐dwelling men. Issue 4 (24th December 2021) - Bauer, Scott R.; Cawthon, Peggy M.; Ensrud, Kristine E.; Suskind, Anne M.; Newman, John C.; Fink, Howard A.; Lu, Kaiwei; Scherzer, Rebecca; Hoffman, Andrew R.; Covinsky, Kenneth; Marshall, Lynn M.
Abstract: Background: Lower urinary tract symptoms (LUTS) are associated with frailty phenotype, a risk factor for functional decline. Our objective was to determine the association between baseline LUTS and 2‐year risk of new functional limitation among older men. Methods: We analyzed data from the Osteoporotic Fractures in Men (MrOS) study with baseline at Year 7 and follow‐up through Year 9. Participants included 2716 community‐dwelling men age ≥ 71 years without any baseline self‐reported functional limitation. LUTS severity (American Urologic Association Symptom Index) was classified as none/mild (score 0–7), moderate (8–19), and severe (20–35). At baseline and follow‐up, men reported their ability to complete several mobility, activities of daily living (ADLs), and cognition‐dependent tasks. Risk was estimated for 3 incident functional limitation outcomes: (1) mobility (any difficulty walking 2–3 blocks or climbing 10 steps), (2) ADL (any difficulty bathing, showering, or transferring), and (3) cognition‐dependent (any difficulty managing money or medications). We used Poisson regression with a robust variance estimator to model adjusted risk ratios (ARR) and 95% CIs controlling for age, site, and comorbidities; other demographic/lifestyle factors did not meet criteria for inclusion. Results: Overall, the 2‐year risk was 15% for mobility, 10% for ADLs, and 4% for cognition‐dependent task limitations. Compared to none/mild LUTS, risk of incident mobility limitations was increased for moderate (ARR = 1.35, 95% CI: 1.12, 1.63) and severe LUTS (ARR = 1.98, 95% CI: 1.48, 2.64). Men were also at higher risk for incident ADL limitations if they reported moderate (ARR = 1.32, 95% CI: 1.05, 1.67) and severe LUTS (ARR = 1.62, 95% CI: 1.07, 2.43). Results were somewhat attenuated after adjusting for the frailty phenotype but remained statistically significant. LUTS were not associated with incident cognition‐dependent task limitations. Conclusions: LUTS severity is associated with incident mobility and ADL limitations among older men. Increased clinical attention to risk of functional limitations among older men with LUTS is likely warranted.